2005
DOI: 10.1038/sj.cdd.4401559
|View full text |Cite
|
Sign up to set email alerts
|

Daxx is required for stress-induced cell death and JNK activation

Abstract: Daxx has been implicated in the modulation of apoptosis in response to various stimuli. In the nucleus, Daxx interacts and colocalizes with the promyelocytic leukemia protein (PML) into the PML-nuclear body. Moreover, overexpressed Daxx positively modulates FAS-ligand and TGFb-induced apoptosis. However, recent reports indicate that Daxx can also act as an antiapoptotic factor. As most studies on the role of Daxx in cell death have been conducted using tumour cell lines, we analysed the function of Daxx in phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
75
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 40 publications
10
75
0
Order By: Relevance
“…UV elicits cell death through both membrane death receptor-dependent extrinsic death pathway and ROS-dependent intrinsic mitochondria-dependent death pathway (Figure 4). UV rapidly induces robust and sustained JNK through the cytoplasmic membrane receptors such as tyrosine kinase receptors and TNF-R1 (Rosette and Karin, 1996), as well as DNA damage (Lee et al, 1998;Khelifi et al, 2005). Recent studies show that JNK1, but not JNK2 is essential for UV-induced cell death (Liu et al, , 2006.…”
Section: Rela P50mentioning
confidence: 99%
“…UV elicits cell death through both membrane death receptor-dependent extrinsic death pathway and ROS-dependent intrinsic mitochondria-dependent death pathway (Figure 4). UV rapidly induces robust and sustained JNK through the cytoplasmic membrane receptors such as tyrosine kinase receptors and TNF-R1 (Rosette and Karin, 1996), as well as DNA damage (Lee et al, 1998;Khelifi et al, 2005). Recent studies show that JNK1, but not JNK2 is essential for UV-induced cell death (Liu et al, , 2006.…”
Section: Rela P50mentioning
confidence: 99%
“…c-Jun NH2-terminal kinases (JNK), a family of stressactivated protein kinases, may be activated and contribute to apoptotic signal transduction when cells are exposed to multiple forms of stress such as growth factor withdrawal, excitoxic stress, ultraviolet radiation (Kurinna et al, 2004;Hamdi et al, 2005;Khelifi et al, 2005). The target proteins of JNK have the transcription factor c-Jun, which is phosphorylated and activated by JNK, forkhead transcriptional factor which is phosphorylated by JNK and then translocates to nucleus for regulating the transcription of some target genes, and some pro-apoptotic or anti-apoptotic proteins such as Bax and Bcl-2 (Kops et al, 2002;Essers et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Pflegerl et al [32] reported that challenging JUNB ∆ep mice with UVB irradiation enhanced the severity of their lupus-like lesions. It has also been published that DAXX-depleted fibroblasts are resistant to UVB-and oxidative-stress-induced cell death [33]. Presumably, the absence of certain members of the huCOP1-mediated transcriptional cascade leads to an abnormal UVB response.…”
Section: Discussionmentioning
confidence: 99%